2011
DOI: 10.2527/jas.2010-3157
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin and biopterin as biomarkers of immune system activation associated with castration in piglets1

Abstract: Recent reports have shown that stressful situations may affect the production of unconjugated pterins (neopterin and biopterin). The aim of the study was to investigate the effect of castration on neopterin and biopterin plasma concentrations in piglets, using 2 groups of 12 piglets allocated to castrated and uncastrated (control) groups. Pterin concentrations were determined by HPLC with fluorescence detection. Blood samples were also analzyed for leukocyte profiles and plasma cortisol concentrations. A time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…Although biopterin concentrations were elevated at 1 h after castration in CAN and CWL piglets, they did not differ from those of SHAM piglets at the same time points. Modified concentrations of biopterin are in contradiction to our previous study, in which biopterin was not influenced by castration (Marsalek et al 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although biopterin concentrations were elevated at 1 h after castration in CAN and CWL piglets, they did not differ from those of SHAM piglets at the same time points. Modified concentrations of biopterin are in contradiction to our previous study, in which biopterin was not influenced by castration (Marsalek et al 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…The present study confirmed the findings of our previous studies (Smutna et al 2010;Marsalek et al 2011), in which the mean concentration of neopterin in piglets from control groups not subjected to stress or surgical castration was 18 nmol/l and the mean concentration of biopterin was 215 nmol/l, while the concentration of neopterin in adult pigs was significantly lower (5.22 nmol/l) (Breinekova et al 2007). There are no direct methods for measuring the intensity of pain (White et al 1995).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Breinekova et al (2006Breinekova et al ( , 2007 observed elevated levels of both pterin derivates in the serum of transported pigs and concluded that pterins may be a useful biochemical indicator of immune system stimulation by short-term stress. Similarly, Smutna et al (2010) and Marsalek et al (2011) found elevated neopterin levels due to acute stress in pigs. On the contrary, clinical studies on stress in humans showed that glucocorticoids could cause suppression of cell-mediated immunity and consequently could result in decreased neopterin and biopterin concentrations (Atmaca et al, 2002;Kuloglu et al, 2007).…”
Section: Faculty Of Veterinary Hygiene and Ecology University Of Vetmentioning
confidence: 89%